Implementation of PBL Learning Model With The Help of Powerpoint Media and Learning Video on the Measurement Material of Length Units of Grade III Elementary School Kanisius Beringin - Lulus Wiji Lestari (Yayasan Thaifah Manshurah Pekanbaru, 2024)
This research aims to investigate the implementation of the PBL learning model with the help of PowerPoint media and learning videos on unit measurement material for class III students at Kanisius Beringin Elementary School. The research method used is a qualitative descriptive approach using the Case Study method. The challenge in learning the concept of measurement and units at Kanisius Beringin Elementary School is that students are passive in learning, therefore they really need a more interactive approach for students to be more interested in the learning process. The solution is that the PBL approach is chosen as the main learning model, supported by the use of Powerpoint media and learning videos to increase student engagement. The results of the research show that the implementation of PBL with PowerPoint media and learning videos can increase students' interest and understanding regarding units of measurement material. Students look active and enthusiastic about working together in groups, working on LKPD correcting LKPD, and joint evaluations with the results of students already understanding the material. taught. In this way, it can be concluded that the use of the problem based learning (PBL) learning model in mathematics learning long unit material is effective to use